ASSESSMENT OF CAUSES OF INTENSIVE CARE UNIT ADMISSIONS IN RENAL DISEASE PATIENTS: A CROSS-SECTIONAL STUDY - SIKANDAR , MZ; KHAN , MAW; KHAN , AA; JAVED , M; MOEEN , SMH; ASGHAR , A (Biological and Clinical Sciences Research Journal, 2023)
The incidence of End-Stage Renal Disease (ESRD) is on the rise, making it a significant group of patients requiring admission to critical care units. At the same time, the field of Acute Kidney Injury (AKI) has flourished, leading to an increased number of patients with kidney dysfunction in critical care units. Our objective is to assess the causes of admission of patients with kidney disease in a large tertiary care hospital, the Medical Intensive Care Unit (MICU). This is a retrospective electronic case notes study. We collected data from the electronic records of all patients admitted to the MICU with renal problems from 1/7/2022 until 1/10/2022. The data was later analyzed in Microsoft Excel. During the study period, 503 patients were admitted to the MICU, of which 160 (31.8%) had renal disease. The median age was 50 years, ranging from 17 to 92 years. Females accounted for 42.5% of patients, while males accounted for 48.5%. Of the 160 patients, 97 (60.5%) were known to have ESRD, while 63 (39.5%) had AKI due to systemic illness. Fluid overload (40/55, 76.3%), followed by uremic encephalopathy (15/55, 27.2%) and hyperkalemia (12/55, 21.8%), remained the most common causes for initiation of Renal Replacement Therapy (RRT) in 55/97 (56.7%) ESRD patients. The mortality rate was 23.7% (38/160) in renal patients in the medical ICU. Our study highlights the increasing number of patients with kidney disease requiring admission to a medical ICU and their high mortality rate. Sepsis remains the leading cause of admission for ESRD patients on Maintenance Hemodialysis (MHD). At the same time, fluid overload was found to be the primary cause of starting RRT in advanced kidney disease.